What It Means to Believe: Non-Suicidal Self-Injury and Emotion Beliefs Moderate the Relationship Between Emotion Experiences and Emotion Dysregulation - Pizzey H; Boyes ME; Hasking PA; Robinson K (Taylor and Francis Group, 2026)
Objective Although emotion dysregulation is a transdiagnostic risk factor for psychopathology, research typically focuses on dysregulation of negative emotions only. We investigated the contributions of dimensions of emotional experience, emotion beliefs, and non-suicidal self-injury (NSSI) to both negative and positive emotion dysregulation. Method 441 participants (M age = 23.65, 73.5% female, 39.0% with lifetime NSSI) reported their negative and positive emotion reactivity, intensity, perseveration, and dysregulation, as well as their NSSI history and beliefs about the controllability and usefulness of emotions. Results Emotion intensity, perseveration, uncontrollability beliefs, and NSSI were uniquely associated with emotion dysregulation. Counter to predictions, emotion reactivity was associated with less dysregulation. Greater perseveration was associated with greater dysregulation of both negative and positive emotions, but only for participants who believed emotions were uncontrollable. NSSI also moderated the associations between emotion experiences and dysregulation. Among individuals who self-injure, increased emotional intensity was associated with greater dysregulation of positive emotions. Among individuals who self-injure and believed emotions were more useful, increased reactivity was linked to less dysregulation of positive emotions. Conversely, for those without a NSSI history who believed emotions were less useful, increased reactivity was associated with less dysregulation of positive emotion. Conclusion Emotion beliefs are an important mechanism associated with dysregulation of both negative and positive emotion. Positive emotions play a complex role in dysregulation, influenced by cognitive (controllability and usefulness beliefs) and behavioral factors (NSSI), underscoring the need for future research to explore dysregulation of both negative and positive emotions to improve emotional well-being. Highlights Emotion experiences, beliefs, and NSSI are linked toand positive and negative emotion dysregulation. Extended emotions responses are linked to dysregulation only in the context of believing emotions areuncontrollable. Similar emotion beliefs relate differently to experiences and dysregulation depending on NSSI status.
Keywords: Emotion beliefs; emotion dysregulation; meta-cognitive beliefs; non-suicidal self-injury; self-harm